S2 Changing size between the first trimester and five years and asthma outcomes at 18 years of age – a whole population study. (December 2018) - Turner, SW; Aucott, L
Abstract : Background: Reduced length and weight in early life are associated with increased risk for childhood asthma. Our hypothesis was that reduced size during fetal life and early childhood are independently linked to increased risk for asthma throughout childhood. Methods: Routinely acquired fetal, neonatal and maternal data collected between 1987 and 2015 were linked to weight and height at five years (1992–2015), hospital admission data (1987–2005) and primary care prescribing data (2009–2015). The outcomes were any asthma inhaler prescribing and any hospital admission for asthma. General estimating equations were used to relate size in the first, second and third trimester and at birth relative to size at five years. Covariates included offspring sex, age in 2014 and maternal age at delivery, parity, height, weight, smoking status and asthma status. The analysis also considered co-linearity between siblings. Results: Data were linked in 63 930 individuals, the mean age in 2014 was 18.6 (6.9) years and 51% were male. The proportion prescribed any asthma inhaler was 18% (n=11, 798) and 4% had at least one asthma admission (n=2, 740). Measurements in the first, second and third trimesters, at birth and at five years of age were present in 34, 685, 36, 136, 22, 854, 63 280 and 15 788 individuals respectively. The relative risk (RR) for any asthma prescribing was associated with reduced weight in the third trimester (RR per z score difference 1.04 [1.00, 1.09] p=0.040) relative to weight at five years and also greater length at birth (RR per z score difference 1.03 [95% CI 1.00, 1.06] p=0.043) relative to height at five years, independent of covariates. The RR for hospital admission for asthma was increased in association with reduced first trimester length compared to height at five years (RR per z score difference 1.18 [1.06, 1.33] p=0.002) but not with difference in weight. Covariates including maternal asthma, maternal smoking and deprivation were related to risk for asthma outcomes (RR between 1.13 and 1.42). Conclusions: Relative to other factors, catch up in weight and length before birth are associated with small increases in risk for asthma outcomes at 18 years of age.